CPU implementation using only logisim simulator to achieve computer architecture learning outcome - Mochammad Hannats Hanafi Ichsan; Wijaya Kurniawan (Institute of Advanced Engineering and Science, 2020)
This paper proposes the design, implementation, and evaluation of an 8-bit CPU architecture in computer organization and architecture (COA) course for Undergraduate Computer Engineering using only Logisim simulator. The main advantage of using one simulator is the elimination of inefficiency so that students can concentrate more on the course’s content without spending their time just to learn how to use each different type of simulators. To achieve that, a simple CPU architecture is pre-designed and be implemented in Logisim simulator. According to previous researches, Mic-1 CPU architecture is chosen because it is the simplest one and can be easily built using many simple logic gates already existed in the Logisim. To evaluate the desired outcome, students are separated into two different groups. Each group used different type of learning media and material and then their examination scores and satisfaction are compared to each other. Every student belongs to the group that only used Logisim simulator obtained higher score and more than 50% are satisfied with the new learning process and material. Thus, it envisaged that this method will made the delivering learning process in COA course be more efficient than what has happened so far.